Let the angles be x
We are taking both angles as x because they are equal!
➪ <em>T</em><em>h</em><em>u</em><em>s</em><em>,</em><em> </em><em>T</em><em>h</em><em>e</em><em> </em><em>m</em><em>e</em><em>a</em><em>s</em><em>u</em><em>r</em><em>e</em><em> </em><em>o</em><em>f</em><em> </em><em>b</em><em>o</em><em>t</em><em>h</em><em> </em><em>a</em><em>n</em><em>g</em><em>l</em><em>e</em><em>s</em><em> </em><em>i</em><em>s</em><em> </em><em>9</em><em>0</em><em>°</em><em>.</em><em>.</em><em>.</em><em>~</em>
Step-by-step explanation:
a(n) = a +(n-1)d
a=13
d=9-13=5-9=-4
°.° a(n) = 13 +(n–1)-4
hope this helps
Answer:
yeb it is
Step-by-step explanation:
Answer:
x =
Step-by-step explanation:
Given
+ = 1
Multiply through by ab to clear the fractions
bx + ax = ab ← factor out x from each term on the left side
x(b + a) = ab ← divide both sides by (b + a)
x =